Validation of undergraduate science process skills tests: Rasch model analysis - Dian Tauhidah; Ndzani Latifatur Rofi'ah (Research and Development in Education (RaDEn), 2023)
Science process skills are essential skills that students must possess. The science process skills test is needed to facilitate the measurement, so that test instruments are developed. The developed instrument needs to be validated before it is used. The purpose of this study was to validate the science process skills test instrument so that the developed instrument is valid and can be used to measure student abilities. The research was conducted using a quantitative descriptive method. The study population was all biology education students at UIN Walisongo Semarang-Indonesia, with a sample of 75 students selected using a purposive sampling technique. Data were analyzed using Rasch analysis which was divided into several categories, namely map analysis based on the items and research samples, analysis of the suitability of the items, analysis of separation and reliability, and items’ analysis. The results of Rasch's study show that the developed science process skills test for students proves valid. Participating students have fairly even abilities. The results of the validation of the items did not reveal any misconceptions, the questions were on the abilities of the students, and the questions had varying difficulty ranges. The validity of the science process skills test shows that the test instrument can be used to measure students' science process skills. Test instruments can be used as learning evaluation instruments as well as analysis of student problems related to science process skills.